LOCALLY STRESS-CONSTRAINED TOPOLOGY OPTIMIZATION WITH CONTINUOUSLY VARYING LOADING DIRECTION AND AMPLITUDE: TOWARD LARGE-SCALE PROBLEMS - FERNANDO VASCONCELOS DA SENHORA (2022)
PONTIFÍCIA UNIVERSIDADE CATÓLICA DO RIO DE JANEIRO